Diagnostic Criteria of Flow‐Mediated Vasodilation for Normal Endothelial Function and Nitroglycerin‐Induced Vasodilation for Normal Vascular Smooth Muscle Function of the Brachial Artery. Issue 2 (21st January 2020) - Maruhashi, Tatsuya; Kajikawa, Masato; Kishimoto, Shinji; Hashimoto, Haruki; Takaeko, Yuji; Yamaji, Takayuki; Harada, Takahiro; Han, Yiming; Aibara, Yoshiki; Mohamad Yusoff, Farina; Hidaka, Takayuki; Kihara, Yasuki; et al.
Abstract : Background: Diagnostic criteria of flow‐mediated vasodilation (FMD), an index of endothelial function, and nitroglycerin‐induced vasodilation (NID), an index of vascular smooth muscle function, of the brachial artery have not been established. The purpose of this study was to propose diagnostic criteria of FMD and NID for normal endothelial function and normal vascular smooth muscle function. Methods and Results: We investigated the cutoff values of FMD and NID in subjects with (risk group) and those without cardiovascular risk factors or cardiovascular diseases (no‐risk group) in 7277 Japanese subjects (mean age 51.4±10.8 years) from the Flow‐Mediated Dilation Japan study and the Flow‐Mediated Dilatation Japan Registry study for analysis of the cutoff value of FMD and in 1764 Japanese subjects (62.2±16.1 years) from the registry of Hiroshima University Hospital for analysis of the cutoff value of NID. Receiver‐operator characteristic curve analysis of FMD to discriminate subjects in the no‐risk group from patients in the risk group showed that the optimal cutoff value of FMD to diagnose subjects in the no‐risk group was 7.1%. Receiver‐operator characteristic curve analysis of NID to discriminate subjects in the no‐risk group from patients in the risk group showed that the optimal cutoff value of NID to diagnose subjects in the no‐risk group was 15.6%. Conclusions: We propose that the cutoff value for normal endothelial function assessed by FMD of the brachial artery is 7.1% and that the cutoff value for normal vascular smooth muscle function assessed by NID of the brachial artery is 15.6% in Japanese subjects. Clinical Trial Registration: www.umin.ac.jp Unique identifiers: UMIN000012950, UMIN000012951, UMIN000012952, and UMIN000003409